If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = x + -4 Reorder the terms: 2 + 6x = x + -4 Reorder the terms: 2 + 6x = -4 + x Solving 2 + 6x = -4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 6x + -1x = -4 + x + -1x Combine like terms: 6x + -1x = 5x 2 + 5x = -4 + x + -1x Combine like terms: x + -1x = 0 2 + 5x = -4 + 0 2 + 5x = -4 Add '-2' to each side of the equation. 2 + -2 + 5x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = -4 + -2 5x = -4 + -2 Combine like terms: -4 + -2 = -6 5x = -6 Divide each side by '5'. x = -1.2 Simplifying x = -1.2
| 6m+2n+10m= | | 15x+20= | | 0.007=0.7x-0.21 | | 0.555555556(t)+25=-25 | | 1+7x-5x=-21 | | 3(2x-1)+2=5x | | 5a-7=18 | | 0.556(r)+25=-25 | | X-11=-11 | | -x+9+3x=33 | | 5y(-9-3y)=13 | | 0.4(t)-4=2 | | 0.7x+0.38=0.645 | | y=2x^2+6x-108 | | k-5=15 | | 8(x-2)-6x=12-(8x-7) | | s*s=25 | | 3n+5=23 | | -4=6x-5x+4 | | 3x+9=180 | | 2x-18=-6 | | 8x+4(6-x)=2x-16 | | 2x-7y=33 | | 6+7x-5x=16 | | 2-7y=6 | | x+2x=-9 | | x+x*2x=-9 | | 5x+10+6x=10 | | 6x-5=3x+9 | | a+4a=96+a | | 149-5x=22x+20 | | 5(f+2)=2(3-5) |